Diversifikasi Olahan Ikan Patin dan Pelatihan Pembuatan Maggot di Desa Bangkiling Raya Kecamatan Banua Lawas Kabupaten Tabalong - Arfa Agustina Rezekiah; Abdi Fithria; Hafizianor Hafizianor; Noor Arida Fauzana; Candra Candra; Ahmad Yunani; Susilawati Susilawati; Muhammad Ruslan (Universitas Lambung Mangkurat, 2023)
The community empowerment activities of the Community Science and Technology Program are specifically aimed at enhancing the knowledge of the residents, especially the housewives of Bankirin Raya Village, Banua Lawas District, Tabalong District. Meatballs and nuggets are a commodity and easy to make. This empowerment activity encourages communities to start new businesses based on catfish exploitation to increase income for the surrounding communities. Methods used include socialization and counseling, and training. , production management development, program discussion and evaluation. This activity took place in a resident home with 20 participants. Many participants participated in this activity. During the activity, all participants were very enthusiastic to participate in training and coaching. Materials were provided to participants on how to process catfish into economically valuable products. The participant also received online her marketing and financial management guidance and training on starting a new business to improve the participant's skills and knowledge.